2020
DOI: 10.4158/accr-2019-0553
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Thyroid Tissue Masquerading as a Functional Carotid Body Paraganglioma

Abstract: Objective: Ectopic thyroid tissue (ETT) is a rare entity resulting from thyroid gland dysembryogenesis. We present a case of ETT confirmed by histopathology that was misdiagnosed clinically as a carotid body tumor. Methods: A 34-year-old female with a history of thyroidectomy for a goiter presented with 1 year of worsening tachycardia (heart rate ranging from 82 to 111 beats per minute), anxiety, hot flash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…4 There have been only six previously reported cases of ETT at the carotid bifurcation. 5,9,[12][13][14][15] Other unusual locations of ETT include the mediastinum, chest and abdomen. 12 The clinical presentation of our patient was similar to those in previously reported cases -namely, a slow-growing asymptomatic mass.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4 There have been only six previously reported cases of ETT at the carotid bifurcation. 5,9,[12][13][14][15] Other unusual locations of ETT include the mediastinum, chest and abdomen. 12 The clinical presentation of our patient was similar to those in previously reported cases -namely, a slow-growing asymptomatic mass.…”
Section: Discussionmentioning
confidence: 99%
“…5,9,[12][13][14][15] Other unusual locations of ETT include the mediastinum, chest and abdomen. 12 The clinical presentation of our patient was similar to those in previously reported cases -namely, a slow-growing asymptomatic mass. However, on retrospective review it was noted that our patient's preoperative CT scan identified a thyroid gland located in the normal orthotopic position.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations